Multi-vesicular phosphatidylcholine liposomes as vehicles for curcumin in a nutritious drinkable formulation - Madrigal Redondo, German (2017)
Liposomal vesicles are used as a strategy to enhance the stability and bioavailability of its bioactive components. Large part of its characteristics can be attributed to the likeness between the liposomal and biological membranes, given both are formed by amphiphilic molecules. Since they have a vesicular shape, liposomes have the particularity to encapsulate bioactive molecules. This way certain physicochemical and pharma-kinetic characteristics can be enhanced and optimized. Curcumin is a polyphenolic compound with a high therapeutic potential. However, its bioavailability, stability and solubility are relatively low. Due to this, alternatives have been explored, such as liposomes to enhance the aforementioned properties. This investigation yielded a characterization of the physicochemical properties of a nutritious product using curcumin as a bioactive component. Brix levels, pH levels, specific gravity, refraction index and conductivity were measured. Additionally, liposomal vesicles were observed through optical microscopy to recognize structure, size (diameter) and membrane width. Physicochemical characterization indicates that the formula is stable. Also, they can be utilized as quality control for the product and represent a starting point to accomplish possible formula enhancements and optimization. The microscopic observation indicates that liposomes are multi-vesicular and multi-layered structures. This fact indicates that liposomal vesicles are more stable which results favorable for successful formulation.